Diversification of mandarin citrus by hybrid speciation and apomixis - Wu, Guohong Albert; Sugimoto, Chikatoshi; Kinjo, Hideyasu; Azama, Chika; Mitsube, Fumimasa; Talón, Manuel; Gmitter Jr., Frederick G.; Rokhsar, Daniel S. (Springer Nature, 2021)
The origin and dispersal of cultivated and wild mandarin and related citrus are poorly understood. Here, comparative genome analysis of 69 new east Asian genomes and other mainland Asian citrus reveals a previously unrecognized wild sexual species native to the Ryukyu Islands: C. ryukyuensis sp. nov. The taxonomic complexity of east Asian mandarins then collapses to a satisfying simplicity, accounting for tachibana, shiikuwasha, and other traditional Ryukyuan mandarin types as homoploid hybrid species formed by combining C. ryukyuensis with various mainland mandarins. These hybrid species reproduce clonally by apomictic seed, a trait shared with oranges, grapefruits, lemons and many cultivated mandarins. We trace the origin of apomixis alleles in citrus to mangshanyeju wild mandarins, which played a central role in citrus domestication via adaptive wild introgression. Our results provide a coherent biogeographic framework for understanding the diversity and domestication of mandarin-type citrus through speciation, admixture, and rapid diffusion of apomictic reproduction.